2018
DOI: 10.1111/ajt.14561
|View full text |Cite
|
Sign up to set email alerts
|

OPTN/SRTR 2016 Annual Data Report: Heart

Abstract: In 2016, 3209 heart transplants were performed in the United States. New, active listings increased 57% since 2005. The number of adult heart transplant survivors continued to increase, and in 2016, 30,622 recipients were living with heart transplants. Patient mortality following transplant has declined. The number of pediatric candidates and transplants performed also increased. New listings for pediatric heart transplants increased from 454 in 2005 to 624 in 2016. The number of pediatric heart transplants pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
134
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 0 publications
0
134
0
3
Order By: Relevance
“…However, this approach may not capture the varied causes of death in a small but heterogeneous population. Graft failure is the most common cause of death following pediatric HTx, while other common causes include cardiovascular and cerebrovascular disease, infection, and respiratory disease . Variation in causes of death may be difficult to adequately describe with a ML model, especially when focusing on the limited population of pediatric HTx recipients.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach may not capture the varied causes of death in a small but heterogeneous population. Graft failure is the most common cause of death following pediatric HTx, while other common causes include cardiovascular and cerebrovascular disease, infection, and respiratory disease . Variation in causes of death may be difficult to adequately describe with a ML model, especially when focusing on the limited population of pediatric HTx recipients.…”
Section: Discussionmentioning
confidence: 99%
“…This survey analysis showed that more non-kidney transplant candidates (liver, heart, and lung) were willing to accept an HCV-positive organ compared to kidney transplant candidates, although this difference was not statistically significant (p = 0.05). This difference may indicate that the lack of a suitable alternative such as dialysis for the end-stage disease of these organs (although left ventricular assist devices are being used for heart failure) coupled with higher waitlist mortality rates may lead non-kidney transplant candidates toward pursuing HCV-positive organ transplantation more eagerly [2,3,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…1 Of all HF patients, an estimated 150 000-200 000 have advanced (stage D) HF refractory to medical therapy. 3 As a result, durable ventricular assist device (VAD) therapy has been increasingly utilized, and nearly 18 000 continuous-flow VADs (CF-VADs) are implanted annually. 3 As a result, durable ventricular assist device (VAD) therapy has been increasingly utilized, and nearly 18 000 continuous-flow VADs (CF-VADs) are implanted annually.…”
Section: Introductionmentioning
confidence: 99%